2006
DOI: 10.1158/1535-7163.mct-05-0425
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of cisplatin or gemcitabine plus Photofrin/photodynamic therapy: Disjointed cell cycle phase-related activity accounts for synergistic outcome in metastatic non–small cell lung cancer cells (H1299)

Abstract: We compared the effects of monotherapy (photodynamic therapy or chemotherapy) versus combination therapy (photodynamic therapy plus a specific drug) on the nonsmall cell lung cancer cell line H1299. Our aim was to evaluate whether the additive/synergistic effects of combination treatment were such that the cytostatic dose could be reduced without affecting treatment efficacy. Photodynamic therapy was done by irradiating Photofrinpreloaded H1299 p53/p16-null cells with a halogen lamp equipped with a bandpass fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 28 publications
7
57
0
Order By: Relevance
“…Moreover, other study have shown that CDDP combined with DNA caused cell damage (Olas et al, 2006;Salsbury et al, 2006), which could cause apoptosis to some extent. Our study showed that high dose of CDDP caused apoptosis of granulosa cells of ovary at S phase, which was consistent with previous reports that chemotherapeutics have significant role in interfering with cell cycle (Horowitz et al, 2004;Crescenzi et al, 2006;Xu et al, 2007;Hara et al, 2006). Genistein has been shown to have many biological activities, such as anti-cancer, anti-oxidant, antiinflammatory actions and inhibition of tyrosine-specific protein kinases (Akiyama et al, 1987;Rusin et al, 2010;Park et al, 2010;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, other study have shown that CDDP combined with DNA caused cell damage (Olas et al, 2006;Salsbury et al, 2006), which could cause apoptosis to some extent. Our study showed that high dose of CDDP caused apoptosis of granulosa cells of ovary at S phase, which was consistent with previous reports that chemotherapeutics have significant role in interfering with cell cycle (Horowitz et al, 2004;Crescenzi et al, 2006;Xu et al, 2007;Hara et al, 2006). Genistein has been shown to have many biological activities, such as anti-cancer, anti-oxidant, antiinflammatory actions and inhibition of tyrosine-specific protein kinases (Akiyama et al, 1987;Rusin et al, 2010;Park et al, 2010;Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Combination treatment showed dramatically increased cytotoxicity on Hela cells compared with PDT and cisplatin alone (P<0.05) (Figure 3). This is in agreement with other experiments, in which cytotoxic drug such as cisplatin, gemcitabine were found to act synergistically with PDT in vitro (Crescenzi et al, 2004;Crescenzi et al, 2006). In Hela cells, cell viability induced by PDT + 5 mg/L cisplatin was only 6.607±2.656% and which was significantly lower than combination treatment with 0.1, 1.0, 2.5 mg/L cisplatin.…”
Section: Cytotoxicity Of Single or Combination Treatmentsupporting
confidence: 92%
“…A few preclinical studies have been performed to establish potential advantages produced through combination of cisplatin with PDT (Crescenzi et al, 2004;Crescenzi et al, 2006;Uehara et al, 2006;Compagnin et al, 2010;Ge et al, 2011;Kim et al, 2012). He et al (2008) have explored the effects of 5-Aminolevulinic acid photodynamic therapy (5-ALA/PDT) and possible mechanisms involved in the treatment of cervical cancer in vivo an vitro .…”
Section: Synergistic Anticancer Activity Of 5-aminolevulinic Acid Phomentioning
confidence: 99%
“…For growth experiments with drugs, FBS was substituted with DCC-FBS supplemented with testosterone at 10 À7 mol/L as a substrate for aromatase. To experimentally ascertain the dose of drugs required to attain a submaximal effect, dose-response curves were constructed according to a ''fixed dose method'', as previously described (21,22). The growth curve responses of the control cell lines and of cocultured cells were evaluated after treatment with different concentrations of formestane or herceptin alone.…”
Section: Selection Of Cocultures and Doses For Growth Inhibition Expementioning
confidence: 99%